Comparative study of growth responses and screening of inter-specific OTA production kinetics by A. carbonarius isolated from grapes - Lappa, Iliada; Kizis, Dimosthenis; Natskoulis, Pantelis; PANAGOU, EFSTATHIOS (Frontiers in Microbiology, 2015)
The aim of this work was to assess OchratoxinA (OTA) production of different Aspergillus carbonarius isolates, evaluate their growth profile through different growth measurements, and reveal any underlying correlation between them. Ten different isolates of A. carbonarius isolated from Greek vineyards located in different geographical regions were examined in vitro for their OTA production potential after an incubation period of up to 11 days. All fungal isolates grew on a synthetic grape juice medium (SGM) similar to grape composition at optimum conditions of temperature and water activity (25°C and 0.98 aw). Samples for OTA determination were removed at 3, 5, 7, 9, and 11 days of growth and analyzed by HPLC. Based on OTA measurements the isolates were characterized by diverse OTA production ranging from 50 to 2000 ppb at day 11. The different fungal growth responses (colony diameter, colony area, biomass, biomass dry weight, and colony density) have been measured and correlated with toxin production by means of principal components analysis (PCA), confirming satisfactory correlation and explained over 99% of data variability. Leudeking-Piret model was also used to study OTA production with time, revealing a mixed-growth associated trend and pointing a fail-safe model with slightly better prediction through colony area. This approach contributes to the assessment of correlation between mycotoxin production and different methods of fungal growth determination in relation to time.